Growth performance of pigs fed low-protein diets supplemented with crystalline amino acids at different growth stages - Inho Cho; Changsu Kong (Animal Bioscience)
Objective This study aimed to investigate the impact of reducing dietary crude protein (CP) coupled with supplementation of indispensable amino acids (AA) on growth performance of pigs at different growth stages. Methods A total of 126 (63 barrows and 63 gilts), 90 (45 barrows and gilts), and 72 (36 barrows and 36 gilts) pigs with average weights of 9.8±1.62, 30.6±2.31, and 58.3±2.95 kg in the nursery, growing, and finishing stages, respectively, were assigned to three dietary treatments with six replicates in a randomized complete block design. The pigs had ad libitum access to water and fed three experimental diets, each supplemented with all indispensable AA and subjected to a 2% reduction in CP from the upper limits of 18%, 16%, and 16% established for the nursery, growing, and finishing stages, respectively. Results In the nursery stage, from 0 to 2 weeks, reducing dietary CP concentrations decreased average daily feed intake (ADFI; linear, p = 0.04). From 2 to 4 weeks, dietary CP reduction decreased average daily gain (ADG; linear, p<0.01; quadratic, p = 0.02), ADFI (linear, p = 0.04), and gain-to-feed ratio (G:F; linear, p = 0.01). From 0 to 4 weeks, reduction in dietary CP concentrations decreased ADG (linear p<0.01), and G:F (linear, p = 0.01). In the growing stage, the dietary CP reduction did not affect growth performance. During the finishing stage, decrease in dietary CP concentrations decreased ADFI from 3 to 6 weeks (quadratic, p<0.01) and 0 to 6 weeks (quadratic, p = 0.01). Conclusion Dietary CP reduction with indispensable AA supplementation potentially decreases the growth performance of nursery pigs but may not decrease the growth performance of growing and finishing pigs.